Perancangan WEB Profil Dengan Metode UCD pada LKP Dinasty Trenggalek - Wasyarofah, Khoirul Alpadilla Bela; Aszari, Vina Ayu; Izzati, Afifah Nurul (Fakultas Sains dan Teknologi, Universitas Ibrahimy, 2026)
The development of information technology requires educational institutions to innovate in the digital dissemination of information. The Trenggalek Dynasty Course and Training Institute (LKP) previously faced obstacles in delivering profile information and participant registration because it was still done manually using brochures. This research aims to design a profile website for the Trenggalek Dinasty LKP as an interactive information media that is easily accessible to the public. The method used is User Centered Design (UCD), which emphasizes user involvement in every stage of design, starting from identifying the context of use, determining user needs, designing design solutions, to evaluating the results. The research results show that the resulting website interface design is in accordance with user needs, informative, and easy to use. This website is able to display information about the institution's profile, vision and mission, achievements, activities, and institution contacts with an attractive appearance and clear navigation. By implementing the UCD method, the LKP Dinasty Trenggalek profile website is expected to increase the credibility of the institution and simplify the promotion and registration process for new students.